2022
DOI: 10.1021/acs.jpcc.1c10258
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Origin of Defect-Induced Raman Mode in WS2 Monolayers via Density Functional Perturbation Theory

Abstract: Transition metal dichalcogenides (TMDs) are being actively studied in nextgeneration semiconductor applications owing to their excellent optoelectronic properties. Therefore, numerous defect-related studies have been conducted to improve TMD quality. In the study of defects, Raman spectroscopy is widely used to obtain information regarding the defects on a surface. A single sulfur-vacancy-induced Raman peak was recently reported. However, the origin of this vibrational mode has not yet been identified. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, Lee et al reported the appearance of higher-frequency defect-related modes in WS 2 monolayers and a red-shift of the A′ 1 mode due to S vacancies . Recently, Yoo et al reported that the defect mode in single S-vacant 1L-WS 2 originates from A′ 1 phonon vibrations . Following the lead of these prior studies, and noting that the presence of S vacancies was speculated in the original work, we hypothesize that the current discrepancies between the calculated and measured Raman responses occur in part due to the mismatch in S vacancies between the two systems.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Furthermore, Lee et al reported the appearance of higher-frequency defect-related modes in WS 2 monolayers and a red-shift of the A′ 1 mode due to S vacancies . Recently, Yoo et al reported that the defect mode in single S-vacant 1L-WS 2 originates from A′ 1 phonon vibrations . Following the lead of these prior studies, and noting that the presence of S vacancies was speculated in the original work, we hypothesize that the current discrepancies between the calculated and measured Raman responses occur in part due to the mismatch in S vacancies between the two systems.…”
Section: Resultsmentioning
confidence: 70%
“…49 Recently, Yoo et al reported that the defect mode in single S-vacant 1L-WS 2 originates from A′ 1 phonon vibrations. 60 Following the lead of these prior studies, and noting that the presence of S vacancies was speculated in the original work, 21 we hypothesize that the current discrepancies between the calculated and measured Raman responses occur in part due to the mismatch in S vacancies between the two systems. The discrepancies above are largely resolved by incorporating S vacancies into the model.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…These two last modes are better observed in resonance conditions. 48 Several other second (or more)-order Raman peaks situated between 240 and 290 cm −1 are also enhanced due to the exciton−phonon resonance effect, as discussed by Berkdemir et al 51 Following the same idea, the band around 298 cm −1 might be assigned as a double resonance process involving two ZA(M) phonons, 52,53 although several works attribute this feature to a fourth-order process. 51,54 Figure 2b shows a typical room-temperature photoluminescence spectrum of a WS 2 monolayer.…”
Section: ■ Materials and Methodsmentioning
confidence: 95%
“…Modulated point structures, for example, single atomic vacancies, often induce folded Brillouin zones in prime structures, and then result in attached phonon states. 368 With the comprehension of the centroid transformation of modulated structures, phonons present changes in frequencies, serving as quasi-particles describing the lattice vibration. Thus, the isotopic doping condition indicates a shift in the Raman characteristic peaks, which has been utilized to reveal the growth mechanism of graphene.…”
Section: Property Transformationsmentioning
confidence: 99%